2021
DOI: 10.1007/s00784-021-03962-0
|View full text |Cite
|
Sign up to set email alerts
|

Complementing the pulp proteome via sampling with a picosecond infrared laser (PIRL)

Abstract: Objectives The aim of this investigation was the detailed analysis of the human pulp proteome using the new picosecond infrared laser (PIRL)-based sampling technique, which is based on a completely different mechanism compared to mechanical sampling. Proteome analysis of healthy pulp can provide data to define changes in the proteome associated with dental disease. Material and methods Immediately after extraction of the entire, undamaged tooth, 15 wisdom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
4
3
0
Order By: Relevance
“…Despite differences in total detected proteins, GO enrichment analysis based on biological process terms in the present study highlighted similar functions as compared to previous studies of normal permanent dental pulp tissue (Fig. S1 ) [ 19 21 , 23 ]. For supernumerary permanent teeth, a total of 1,093 proteins were detected (Supplementary Table 3).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Despite differences in total detected proteins, GO enrichment analysis based on biological process terms in the present study highlighted similar functions as compared to previous studies of normal permanent dental pulp tissue (Fig. S1 ) [ 19 21 , 23 ]. For supernumerary permanent teeth, a total of 1,093 proteins were detected (Supplementary Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…For supernumerary permanent teeth, a total of 1,093 proteins were detected (Supplementary Table 3). Interestingly, according to previous reports and this study, there have only been roughly 66 − 4,332 identified proteins in dental pulp tissue thus far (Supplementary Table 5) [19][20][21][22][23]. This is a relatively low number when compared to the number of proteins found in other tissue or in a single cell that have been previously reported [33,34].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations